Apparent digestibility and protein quality evaluation of selected feed ingredients in Seriola dumerili. Issue 4 (12th March 2019) - Tomás‐Vidal, Ana; Monge‐Ortiz, Raquel; Jover‐Cerdá, Miguel; Martínez‐Llorens, Silvia
Abstract : The apparent digestibility coefficients (ADCs) of dry matter, crude protein, crude lipid, and amino acids in fish, krill, squid, meat, defatted krill, soybean, wheat gluten, wheat, camilina, pea, sunflower, and fava bean meals were determined for juvenile Seriola dumerili . The results showed that the ADC of dry matter for yellowtail ranged from 57.7 to 87.2% for animal ingredients and from 42.2 to 82.2% for plant ingredients. An ADC of protein exceeding 90% was observed in fishmeal, while camilina meal and fava bean meal presented the lowest values. Pea meal presented the lowest lipid ADC (83.5%). The availabilities were generally higher in animal ingredients than those in vegetal ones. Except camilina and fava bean meal, the other ingredients appear to be favorable for S. dumerili diets, especially the ones from animal sources. Lower case chemical score values (minimum value from amino acid ratios [AARs]) were obtained in some vegetal ingredients (14–18%), while the highest ones were observed in marine ingredients (69–88%). According to Oser's Index, the most balanced protein for yellowtail with regard to essential amino acids was in krill, defatted krill, and fishmeal (92–96%). So, animal sources are suitable as protein ingredients, but they could be enhanced through some essential amino acid supplementation.